Organic Arsenical Exposure Stimulates Atherosclerosis through Oxidative Stress Increase and Adhesion Molecule Expression - Afeez Adekunle Ishola, Norlelawati A.Talib, Naznin Muhammad, Zunariah Buyong, Abdul Hadi Mohamed, Yiyi Myint, Niza Samsuddin, Radiah Abdul Ghani, Norzamzila Abdullah (Journal of Applied Pharmaceutical Science, 2016)
Approximately 100 million people are exposed to arsenic worldwide, majorly through drinking water and anthropogenic activities. Monosodium methylarsonate (MSMA) is a potent organoarsenical content of herbicides used in many Asian countries. Epidemiological studies have linked inorganic arsenic exposure with atherosclerosis, whereas organoarsenicals toxicological studies are scanty. Paraoxonase 1 (PON1) enzyme suppresses systemic Ox-LDL generation, thereby preventing atherosclerosis. We investigated effects of MSMA oral exposure on PON1, lipid peroxidation and atherosclerosis development. Five groups (n=11) of Sprague-Dawley rats received daily intubation of MSMA at 0 (control), 42.1, 63.2, 126.4 and 210.7 mg/kg BW respectively for 16 weeks. Serum samples were analysed for PON1 activities, Ox-LDL and MDA levels. Histomorphometric evaluation (H&E and VVG) and immunohistochemistry (VCAM-1 and ICAM-1) were done on aorta. High mortality rate led to discontinuation of 126.4 and 210.7 mg/kg BW treatment groups. Groups treated with 42.1 and 63.2 mg/kg B.W. MSMA had a significantly higher MDA (p=0.004,CI: 2.73-0.82) and Ox-LDL (p
Keywords: Atherosclerosis, Organic arsenic, Monosodium methylarsonate (MSMA), Paraoxonase 1 (PON1), Lipid peroxidation, adhesion molecules (VCAM-1 and ICAM-1).